2017
DOI: 10.1177/1363459317739437
|View full text |Cite
|
Sign up to set email alerts
|

Depression at work, authenticity in question: Experiencing, concealing and revealing

Abstract: Australia and the UK have both introduced policies to protect employees who experience mental illness, including depression. However, a better understanding of the issues workers face (e.g. sense of moral failure) is needed for the provision of appropriate and beneficial support. We analysed 73 interviews from the UK and Australia where narratives of depression and work intersected. Participants encountered difficulties in being (and performing as if) 'authentic' at work, with depression contributing to confus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
9
0
5
Order By: Relevance
“…Further, some studies suggest that students prefer and can benefit from mentors who share their same identity, especially if their identities are stigmatized; so far, this has been demonstrated with gender and race/ethnicity (Blake-Beard et al 2011;Dee 2004;Patton and Bondi 2015). Because both students and potential research mentors are unlikely to reveal their CSIs in professional settings (Cooper et al 2019a;Cooper and Brownell 2016;Ridge et al 2019), finding a mentor with the same CSI is likely extremely difficult; and to our knowledge, there is little research about whether same-identity mentoring is effective for students with CSIs in the context of undergraduate research.…”
Section: Concealable Stigmatized Identities In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, some studies suggest that students prefer and can benefit from mentors who share their same identity, especially if their identities are stigmatized; so far, this has been demonstrated with gender and race/ethnicity (Blake-Beard et al 2011;Dee 2004;Patton and Bondi 2015). Because both students and potential research mentors are unlikely to reveal their CSIs in professional settings (Cooper et al 2019a;Cooper and Brownell 2016;Ridge et al 2019), finding a mentor with the same CSI is likely extremely difficult; and to our knowledge, there is little research about whether same-identity mentoring is effective for students with CSIs in the context of undergraduate research.…”
Section: Concealable Stigmatized Identities In Researchmentioning
confidence: 99%
“…Studies have shown that individuals with CSIs often conceal their identities, particularly in the workplace, for fear of experiencing negative consequences (Cooper et al 2019a;Ridge et al 2019). Specifically, identity management of CSIs can result in strain and stress for individuals (Goffman 2009;Jones and King 2014).…”
Section: Part 1: Understanding Students' Decisions To Reveal or Conceal Their Depression In Undergraduate Researchmentioning
confidence: 99%
“…A lack of adaptive skills, due to reduced psychological flexibility and a different perspective on situations, reduces the capacity to bear responsibilities, which in turn has a negative effect on SAW (30,32,44). Useful coping skills for SAW are: being more alert on signals of reduced mental health, reading and understanding own signals, exerting control over one's own work and workload, balancing positive and negative influences of work, making adjustments and informing colleagues, protecting oneself, taking control, and being assertive (23,28,30,35,37,(45)(46)(47)(48)(49). Also, being highly motivated towards the job increases the likelihood for SAW (23,31,50,51).…”
Section: Middle-range Program Theory 3: Perceived Job Characteristicsmentioning
confidence: 99%
“…environment where supervisors feel comfortable to offer help and support to employees, helps employees to feel motivated and valued, which in turn may have a positive effect on their job performance (29,71). Practical job support from colleagues and managerial support from supervisors, offered continuously while functioning at work despite CMHP, helps to improve WP as the employee experiences trust and empathy (6,29,33,48,51,69,71).…”
Section: Middle-range Program Theory 1: Social Support a Workmentioning
confidence: 99%
“…Internal. The degree to which workers prefer to keep details of their mental illness private is influenced by individual preferences, which are shaped by norms in their family and community (7,10,11). Workers who are accustomed to honesty and frankness are likely to be more open regarding whom they tell and what they disclose than are those whose families or communities placed a high priority on privacy (i.e., "it's nobody else's business").…”
Section: Conditionsmentioning
confidence: 99%